Field-Validated Triplen Harmonic and Neutral Current Mitigation Using an Active Harmonic Filter - Zakky Daniel Haq; Kuntjoro Pinardi; Abdul Multi (International Journal of Engineering Continuity, 2026)
Nonlinear loads in commercial buildings increasingly distort low-voltage distribution systems and may cause excessive neutral-current loading. Third-order triplen harmonics are especially critical in three-phase four-wire systems because their zero-sequence components accumulate in the neutral conductor instead of cancelling among phases. Despite extensive harmonic research, few field-based studies jointly quantify triplen-driven neutral loading, verify Active Harmonic Filter (AHF) performance on an operating commercial site, and confirm IEEE Std 519-2022 compliance within a single case, leaving a practical evidence gap. This paper presents a field-validated assessment of triplen harmonic mitigation in a commercial building distribution system using a shunt Active Harmonic Filter (AHF). Field measurements were obtained at the incoming side of the SDP Amazon Atrium Senen distribution panel using a power quality analyzer, and the results were evaluated using IEEE Std 519-2022. A MATLAB/Simulink model was developed to represent the measured operating condition and support performance interpretation. The model was validated against the field data—accurate for voltage distortion and power factor but under-predicting current distortion—so it is positioned as a trend-analysis rather than a sizing tool. The pre-mitigation condition showed severe current distortion, with phase-current THDi values of 69.27%, 81.47%, and 56.28%, a voltage THD of 5.40%, a neutral current of 96.89 A, and a power factor of 0.82. After AHF operation, the THDi values decreased to 9.87%, 12.18%, and 8.46%, while THDv decreased to 3.35%, neutral current decreased to 23.41 A, and power factor increased to 0.99. Whereas conventional THDi and TDD indices quantify overall distortion but not the zero-sequence burden carried by the neutral conductor, this study introduces a dedicated metric for that burden. The proposed Neutral Harmonic Mitigation Ratio (NHMR) reached 75.84%, indicating substantial reduction of triplen-related neutral loading. Evaluated through Total Demand Distortion under the measured short-circuit ratio, the post-mitigation condition satisfied the IEEE Std 519-2022 current-distortion limit. The results show that a field-validated AHF approach can effectively mitigate triplen harmonic effects and improve power quality in commercial three-phase four-wire distribution systems. Beyond the numerical gains, the field-validated framework gives facility engineers a practical, standards-referenced basis for diagnosing neutral-current risk and planning AHF-based mitigation in commercial power systems.